Evolutionary characterization and pathogenicity of a porcine G9P[23] rotavirus with gene segments linked to canine and giant panda strains - Xi Li; Jingjing Wang; Yuankui Zhang; Yarong Zhao; Wenjun Liu; Yanli Shi (Virus Research)
Porcine rotavirus A (RVA) has emerged as an increasingly consequential zoonotic pathogen, causing severe intestinal disorders across diverse mammalian species, including humans. During of an outbreak that struck nursing piglets with diarrhea, a porcine G9P[23] rotavirus, named as RVA/Pig-wt/China/ZJ03/2022/G9P[23] (hereafter referred to as ZJ03), was identified. To further elucidate the evolutionary diversity of ZJ03, a comprehensive analysis of all genome segments was conducted. The genome constellation was identified as G9-P[23]-I5-R1-C1-M1-A8-N1-T1-E1-H1. Nucleotide sequence identity and phylogenetic analyses indicated that the VP3 and NSP1 genes of ZJ03 are most closely related to the corresponding genes of the giant panda strain and the dog strain, respectively, showing the highest homology at 95.73 % identity and 94.64 %. The remaining genes demonstrated the most intimate relationship with porcine strains. Their highest homology levels ranged from 95.98 % to 99.49 % similarity. Therefore, evidence suggests interspecies transmission and genetic reassortment events between porcine, canine, and giant panda rotavirus strains. To evaluate the pathogenicity of ZJ03 strain, we experimentally infected 3-day-old piglets oral inoculation with the PoRV ZJ03 strain at a dose of 2 × 10^5.5 TCID50/ml per piglet. The infection resulted in severe diarrhea in all piglets, which occurred at 48 h post-infection (hpi), accompanied by sustained viral shedding and characteristic small intestinal villous atrophy, indicating significant damage to the intestinal epithelium. In vitro, ZJ03 exhibited efficient replication kinetics in MA104 cells, reaching peak titers of 10^9.25 TCID50/mL at 36 h post-infection. This study reports the first documented case of a novel porcine G9P[23] rotavirus with gene segments linked to canine and giant panda strains in mainland China, characterized by high viral titer and virulence. The findings highlight the emergence of a previously unrecorded RVA strain with significant virological and ecological implications.